Physicochemical and biochemical properties of an acid soil under potato culture amended with municipal solid waste compost - Marta Domínguez; Remigio Paradelo Núñez; Juan Piñeiro; María Teresa Barral (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose A field trial was conducted on a silty-loam soil under potato culture in NW Spain, to assess the effect of municipal solid waste (MSW) compost in a heavily fertilized acid soil. Methods Three doses of compost (0, 30 and 60 Mg compost ha−1 soil) or inorganic fertilization (~ 140 N: 120 P2O5: 240 K2O kg ha−1 soil) were assayed. The effects of compost on soil physical, chemical (nutrient status and potentially toxic trace elements) and biochemical properties were evaluated after 1 and 5 months. Results Compost addition at the highest dose decreased bulk density and increased soil porosity and soil stability against water erosion. Soil pH, total organic C and N, cation exchange capacity and available P, Ca, Mg and K were also higher in compost-amended soils, whereas no effect on NH4 +-N and NO3 −-N was observed. Compost significantly increased soil microbial biomass and dehydrogenase activity. Due to the high nutrient status in the control soil, potato yield was not increased by compost or inorganic fertilization. A negative consequence of compost addition was the increased extractability of trace metals such as Zn, Cu, Pb and Ni, although their total concentrations in soil or in potato tubers did not increase with respect to the control. Conclusions Overall, results show that positive effects of MSW compost can be expected even in rich soils that do not need fertilization for maintaining their productive function in the short-term. These positive effects prove the benefits of recycling urban wastes in agricultural soils as a sustainable way of waste management.